Rhododendron lowii - Tsen, S.; Mohd Yusof, Nur Adillah,M.Y.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Rhododendron lowii is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 72 km2 and 11,266 km2, respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. It is known from at least six protected areas and currently there is no threat to the population. Hence, it is assessed as Least Concern. Rhododendron lowii is endemic to Sabah, Malaysia.